2022
DOI: 10.1039/d1ee03097c
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the activity, mechanism and application of selective electrosynthesis of ammonia from nitrate on cobalt phosphide

Abstract: Electrochemical reduction of nitrate to ammonia (nitrate reduction reaction, NO3-RR) under ambient conditions, which overcomes the drawbacks of energy-intensive Haber−Bosch reaction and low-efficient N2 electroreduction, is one of the alternatives...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
132
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(133 citation statements)
references
References 37 publications
1
132
0
Order By: Relevance
“…Furthermore, theoretical calculations revealed that NO3 − was adsorbed more easily than H on CoP (112), and the PDS was identified as *NO2 to *NO2H. In addition, Liu and his colleagues [418] The electrocatalytic activities of various Co-containing spinel oxides for NO3RR were investigated by our group. We first reported a comparison of monolithic electrocatalysts, i.e., 3D NiCo2O4 and Co3O4 integrated on CC, for selectively converting NO3 − to NH3 [419].…”
Section: Electrochemical Reduction Of Nitrogen Oxyanionsmentioning
confidence: 99%
“…Furthermore, theoretical calculations revealed that NO3 − was adsorbed more easily than H on CoP (112), and the PDS was identified as *NO2 to *NO2H. In addition, Liu and his colleagues [418] The electrocatalytic activities of various Co-containing spinel oxides for NO3RR were investigated by our group. We first reported a comparison of monolithic electrocatalysts, i.e., 3D NiCo2O4 and Co3O4 integrated on CC, for selectively converting NO3 − to NH3 [419].…”
Section: Electrochemical Reduction Of Nitrogen Oxyanionsmentioning
confidence: 99%
“…Well-defined surface studies provide detailed mechanistic information on the surface interaction of adsorption and intermediate species and can reveal the structure-activity relationship of different surfaces. 29–33 However, it is extremely challenging to acquire in situ spectroscopic evidence from these Cu( hkl ) surfaces while directly monitoring CO 2 RR-related surface species (Fig. 1a), thus making our understanding of the exact CO 2 RR mechanism uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, as demonstrated by XPS analysis, the dominant presence of oxidized BO x and PO x species on the surfaces of PdBP NAs provides electron-deficient B and P sites, which serve as Lewis acid sites to not only enhance the adsorption of nitrate ions that are weak Lewis bases but also effectively prevent overactive hydrogen evolution. 39,53–60 On the other hand, the lattice strain induced by B and P co-doping makes some of the adsorbed hydrogen atoms (*H) survive, desorb away from the catalyst surface and ultimately evolve into hydrogen radicals (·H) existing in the reaction medium, which can reduce kinetic barriers in hydrogenating intermediates to ammonia. 43,44,50,61,62 Collectively, the modification of the Pd crystal structure with metalloid B and nonmetal P elements can modulate the electron configuration of the active center at the atomic level, thus inducing lattice strain and enabling the production of more moderate hydrogen adsorption/desorption intensities.…”
Section: Resultsmentioning
confidence: 99%